THE ADVANTAGES OF OPTIMIZING THE PROPHYLAXIS DIET FOR RESTORING THE HEALTH OF WORKERS OF WASTE RECYCLING ENTERPRISES - Alimukhamedov D. Sh.; Kenyaev Y. M. (Innovate Conferences, 2025)
Today, the problem of waste is becoming one of the most pressing environmental issues in the world. Analyses show that in recent years, household and industrial waste has been increasing year by year. In particular, in the 21st century, the growth of household waste by 60% began to have a very negative impact on environmental sustainability. In this regard, along with the economic efficiency of enterprises producing secondary products from waste, the health of workers working there is also one of the pressing problems today. In order to increase the resistance of workers to various diseases, increase the stability of their immune system, it is necessary to study preventive diets and optimize food products that are beneficial to the workers' body.